Extracellular matrix proteins matrix metallopeptidase 9 (MMP9) and soluble intercellular adhesion molecule 1 (sICAM‐1) and correlations with clinical staging in euthymic bipolar disorder. (March 2016) - Reininghaus, Eva Z; Lackner, Nina; Birner, Armin; Bengesser, Susanne; Fellendorf, Frederike T; Platzer, Martina; Rieger, Alexandra; Queissner, Robert; Kainzbauer, Nora; Reininghaus, Bernd; McIntyre, Roger S; Mangge, Harald; et al.
Abstract : Objectives: Matrix metallopeptidase 9 (MMP9) and soluble intercellular adhesion molecule 1 (sICAM‐1) are both involved in the restructuring of connective tissues. Evidence also implicates MMP9 and sICAM in cardiovascular and neoplastic diseases, where blood levels may be a marker of disease severity or prognosis. In individuals with bipolar disorder (BD), higher risk for cardiovascular illness has been extensively reported. Methods: The aim of this investigation was to measure and compare peripheral levels of serum MMP9 and sICAM in adults with euthymic BD and healthy controls (HC). Furthermore, we focussed on correlations with illness severity and metabolic parameters. Results: MMP9 levels among the BD sample (n = 112) were significantly higher than among the HC (n = 80) (MMP9: F = 9.885, p = 0.002, η 2 = 0.058) after controlling for confounding factors. Patients with BD in a later, progressive stage of disease showed significantly higher MMP9 as well as sICAM‐1 levels compared to patients with BD in an earlier stage of disease (MMP9: F = 5.8, p = 0.018, η 2 = 0.054; sICAM‐1: F = 5.6, p = 0.020, η 2 = 0.052). Correlation analyses of cognitive measures revealed a negative association between performance on the d2 Test of Attention and MMP9 ( r = −0.287, p = 0.018) in the BD sample. Despite the sample being euthymic (i.e., according to conventional criteria) at the time of analysis, we found significant correlations between MMP9 as well as sICAM‐1 and subthreshold depressive/hypomanic symptoms. Conclusions: A collection of disparate findings herein point to a role of MMP9 and cICAM‐1 in the patho‐progressive process of BD: the increased levels of serum MMP9 and sICAM‐1, the correlation between higher levels of these parameters, progressive stage, and cognitive dysfunction in BD, and the positive correlation with subthreshold symptoms. As sICAM‐1 and MMP9 are reliable biomarkers of inflammatory and early atherosclerotic disease, these markers may provide indications of the presence of occult cardiovascular disease in this highly at‐risk population.